Dual Action of Curcumin as an Anti- and Pro-Oxidant from a Biophysical Perspective - Agnieszka Wolnicka-Glubisz; Anna Wisniewska-Becker (Antioxidants, 2023)
Curcumin, a natural polyphenol widely used as a spice, colorant and food additive, has been shown to have therapeutic effects against different disorders, mostly due to its anti-oxidant properties. Curcumin also reduces the efficiency of melanin synthesis and affects cell membranes. However, curcumin can act as a pro-oxidant when blue light is applied, since upon illumination it can generate singlet oxygen. Our review aims to describe this dual role of curcumin from a biophysical perspective, bearing in mind its concentration, bioavailability-enhancing modifications and membrane interactions, as well as environmental conditions such as light. In low concentrations and without irradiation, curcumin shows positive effects and can be recommended as a beneficial food supplement. On the other hand, when used in excess or irradiated, curcumin can be toxic. Therefore, numerous attempts have been undertaken to test curcumin as a potential photosensitizer in photodynamic therapy (PDT). At that point, we underline that curcumin-based PDT is limited to the treatment of superficial tumors or skin and oral infections due to the weak penetration of blue light. Additionally, we conclude that an increase in curcumin bioavailability through the using nanocarriers, and therefore its concentration, as well as its topical use if skin is exposed to light, may be dangerous.